Perkembangan Pendidikan Indonesia Abad 16-19 - Heny Kusmawati; Aji Zulfa Kummala; Fadhila Khoirun Ni’mah; Siti Nur Sa’idah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Education is an effort and process to gain one's knowledge, skills and expertise through learning activities in schools or madrasas. Even outside the school can be held learning activities. With education we can give birth to intelligent and skilled nation's children. In addition, education is also one of the drivers of the progress of a country. The more the quality of education in Indonesia increases, the more Human Resources in Indonesia will also increase. The history of education in Indonesia has taken place before Indonesia's independence. In the 16th century, the Portuguese came to colonize Indonesia and the first Europeans to come to Indonesia were then followed by the Spanish. When Portuguese came to Indonesia, the education system in Indonesia was heavily influenced by world religions such as Christianity. In addition, Portuguese also provides learning to read, write and even count. Education in Indonesia can be independent because of the efforts of the heroes who have fought to liberate Indonesia. One of the heroes like R.A Kartini who fought for the position and education of her people, especially women. And don't forget, Ki Hadjar Dewantara, who we call none other than the Father of National Education, who has struggled to advance education in Indonesia. Apart from these two figures, there are many other heroes who have struggled to advance education in Indonesia.